Analysis of the Utilization of Hypnobirthing in Mother in Labor Process in Eka Sri Wahyuni Clinic, Medan Denai District - Siregar, Mislaini Barkah; Kahar, Irawaty; Lubis, Andi Ilham (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Childbirth is a thing that is eagerly awaited by a woman who has a family. For a woman, the labor process is often a scary feeling, because they imagine the pain that will be experienced when giving birth later. As a result, the fear that is owned is higher and causes the pain that will be experienced when giving birth later. As a result, the fear that is possessed is higher and causes the pain to be stronger than it should be because in their minds they have been implanted that the process of labor is painful. The onset of labor pain and the consequences of labor pain can be attempted to reduce to relieve labor anxiety and pain, one of which is the hypnosis method